6-Bromo-3-methyl-1H-imidazo[4,5-b]pyridin-2(3H)-one - Ghacham, H.B.; Rodi, Y.K.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(7)H(6)BrN(3)O, was obtained from the reaction of 6-bromo-1H-imidazo[4,5-b]pyridin-2(3H)-one with methyl iodide. All non-H atoms lie in a common plane [r.m.s deviation = 0.017 (1) angstrom]. The amino group is a hydrogen-bond donor to the carbonyl group of an inversion-related molecule, the pair of hydrogen bonds giving rise to a hydrogen-bonded dimer.